Ligand-centred redox activation of inert organoiridium anticancer catalysts. Issue 21 (15th May 2020) - Zhang, Wen-Ying; Banerjee, Samya; Hughes, George M.; Bridgewater, Hannah E.; Song, Ji-Inn; Breeze, Ben G.; Clarkson, Guy J.; Coverdale, James P. C.; Sanchez-Cano, Carlos; Ponte, Fortuna; Sicilia, Emilia; Sadler, Peter J.
Abstract : Organometallic complexes with novel activation mechanisms are attractive anticancer drug candidates. Abstract : Organometallic complexes with novel activation mechanisms are attractive anticancer drug candidates. Here, we show that half-sandwich iodido cyclopentadienyl iridium(iii ) azopyridine complexes exhibit potent antiproliferative activity towards cancer cells, in most cases more potent than cisplatin. Despite their inertness towards aquation, these iodido complexes can undergo redox activation by attack of the abundant intracellular tripeptide glutathione (GSH) on the chelated azopyridine ligand to generate paramagnetic intermediates, and hydroxyl radicals, together with thiolate-bridged dinuclear iridium complexes, and liberate reduced hydrazopyridine ligand. DFT calculations provided insight into the mechanism of this activation. GS − attack on the azo bond facilitates the substitution of iodide by GS −, and leads to formation of GSSG and superoxide if O2 is present as an electron-acceptor, in a largely exergonic pathway. Reactions of these iodido complexes with GSH generate Ir-SG complexes, which are catalysts for GSH oxidation. The complexes promoted elevated levels of reactive oxygen species (ROS) in human lung cancer cells. This remarkable ligand-centred activation mechanism coupled to redox reactions adds a new dimension to the design of organoiridium anticancer prodrugs.